TOMFuN: A tensorized optical multimodal fusion network - Xian Xiao; Yequan Zhao; Yuan Yuan; Geza Kurczveil; Marco Fiorentino; Ray Beausoleil; Zheng Zhang (APL Machine Learning)
This paper proposes a real-size, single-shot, high-speed, and energy-efficient tensorized optical multimodal fusion network (TOMFuN) on an electro-photonic large-scale III–V-on-Si in-memory compute engine. The TOMFuN architecture leverages a memory-efficient and low-complexity self-attention for the embedding network for the text information and tensor-train and CANDECOMP/PARAFAC decompositions for compressing the model parameters in the large-scale fully connected layers. Compared to full-size counterparts, our proposed network maintains a compatible inference accuracy in multimodal sentiment analysis tasks while requiring 92.8× fewer model parameters and 51.3× fewer hardware resources. Furthermore, the impact of photonic device imperfections on the TOMFuN architecture is investigated. The simulation results show that noise-aware on-chip training exhibits superior robustness. Finally, chip performance analysis shows that our TOMFuN inference accelerator has 230.73 PetaOps computational speed, 6.51 TOPS/W power efficiency, and 2.7 µs latency with the input dimensions of 1024.